The Role of Facilitators in Implementation of “Espacios para Crecer”: Formative Evaluation of the Program with Young Workers “Edúcame Primero, Colombia” - Holgado Ramos, Daniel; Laboratorio de Redes Personales y Comunidades Departamento de Psicología Social Universidad de Sevilla (Pontificia Universidad Javeriana, 2014)
The article describes the formative evaluation of an educational intervention program with working children in Barranquilla (Colombia). An international team of evaluators conducted qualitative interviews with a sample of facilitators (n = 8), families of participants (n = 38) and teachers of schools where the program was implemented (n = 40). The interviews focused on the implementation process and discussed the role of facilitators, which administered the program and develop strategies for community mediation. The results show the connection between the processes of community involvement and the effectiveness of the intervention. The facilitators connect the program with the organizational and community contexts. In the implementation process, the role of facilitators consisted on (a) to adjust the program to the peculiarities and difficulties of the context, (b) to exchange good practices, and (c) to mediate with teachers and families involved. While the role of mediation and community adjustment of the facilitators were planned in the design, the formation of an informal group among the most active applicators affects to the central components of the program. Paradoxically, this dynamic improved the implementation and outcomes. In this context we discuss the lessons learned in the prevention of child labor.